Redescription and placement of the Oriental Scaphepyris rufus Kieffer (Hymenoptera: Bethylidae) - Lanes, G. O.; Azevedo, C. O. (Zootaxa, 2007)
The Sclerodermini (Bethylidae: Epyrinae) genus Scaphepyris Kieffer and its single species, S. rufus Kieffer, are known only from Indonesia, and are revised. The genus is characterized by having the clypeus produced medially with the apical margin subangulate, the mesopleuron with a large, long upper groove, the ocelli and wings absent, the mid tibiae strongly spinose, the eyes extremely reduced, and a constriction between the propodeum and the mesonotum. These two latter conditions place it in Pristocerinae. A key for the Pristocerinae genera where females are known is provided.